2018
DOI: 10.1371/journal.pone.0192150
|View full text |Cite
|
Sign up to set email alerts
|

Molecular elucidation of a new allelic variation at the Sg-5 gene associated with the absence of group A saponins in wild soybean

Abstract: In soybean, triterpenoid saponin is one of the major secondary metabolites and is further classified into group A and DDMP saponins. Although they have known health benefits for humans and animals, acetylation of group A saponins causes bitterness and gives an astringent taste to soy products. Therefore, several studies are being conducted to eliminate acetylated group A saponins. Previous studies have isolated and characterized the Sg-5 (Glyma.15g243300) gene, which encodes the cytochrome P450 72A69 enzyme an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…). Sg‐1 and Sg‐5 were used as controls: the former is involved in the attachment of a sugar chain at the C‐22 position of SS‐A (Sayama et al ., ), and the latter is involved in the conversion of SS‐B to SS‐A (Yano et al ., ; Sundaramoorthy et al ., ). In addition, β‐amyrin synthase ( BAS1 ) involved in β‐amyrin production was also used as a control.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…). Sg‐1 and Sg‐5 were used as controls: the former is involved in the attachment of a sugar chain at the C‐22 position of SS‐A (Sayama et al ., ), and the latter is involved in the conversion of SS‐B to SS‐A (Yano et al ., ; Sundaramoorthy et al ., ). In addition, β‐amyrin synthase ( BAS1 ) involved in β‐amyrin production was also used as a control.…”
Section: Resultsmentioning
confidence: 97%
“…S2; Sayama et al ., ). Recently, a hydroxylase gene, Sg‐5 , which encodes the CYP72A69 enzyme responsible for the biosynthesis of SS‐A, has been characterized in soybean (Yano et al ., ; Sundaramoorthy et al ., ). DDMP saponins contain a DDMP moiety at the C‐22 position and a single sugar chain at the C‐3 hydroxyl position of the aglycone known as soyasapogenol B (SS‐B; 3β,22β,24‐trihydroxyolean‐12‐ene) (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the CWLGC germplasms were studied for their natural variations in saponin contents and were used to help identify different group-A acetylsaponin-deficient mutants [32,[104][105][106]. The wild soybean soyasaponin mutants from CWLGC have been used to identify and characterize the genes involved in the saponin biosynthesis pathway, e.g., Sg-1 locus (CWS2133), sg-5 locus (CWS5095), and Sg-6 locus [33,105,[107][108][109]. In addition to saponins, wild soybean accessions at the CWLGC have also been screened for the presence of Kunitz trypsin inhibitor polymorphism, alpha-linolenic acid concentration, and soyisoflavone profile diversity [110][111][112][113].…”
Section: In Situ Conservation Of G Soja At Cwlgcmentioning
confidence: 99%
“…Moreover, the CWLGC germplasms were studied for their natural variations in saponin contents and were used to help identify different group-A acetylsaponin-deficient mutants [104][105][106][107]. The wild soybean soyasaponin mutants from CWLGC have been used to identify and characterize the genes involved in the saponin biosynthesis pathway, e.g., Sg-1 locus (CWS2133), sg-5 locus (CWS5095), and Sg-6 locus [33,106,[108][109][110].…”
Section: In Situ Conservation Of G Soja At Cwlgcmentioning
confidence: 99%
“…Members of the CYP716 subfamily of P450s catalyze various oxidations on the -amyrin backbone, including the three-step oxidation of -amyrin at the C-28 position to yield oleanolic acid by CYP716A12 (Carelli et al 2011;Miettinen et al 2017), the C-16α hydroxylation of -amyrin by CYP716Y1 , and the C-3 oxidation by CYP716A14 (Moses et al 2015). In addition, CYP72A154 oxidizes -amyrin at the C-30 position (Seki et al 2011) and several P450s have been identified that further modify oxidation products of -amyrin, such as MtCYP72A61 and GmCYP72A69 (Sundaramoorthy et al 2018;Yano et al 2016) that hydroxylate 24-hydroxy--amyrin at the C-22 and C-21 positions, respectively, in soyasaponin biosynthesis, MtCYP72A68 that oxidizes C-23 of oleanolic acid, and MtCYP72A67 that catalyzes oxidation at C-2 position (Biazzi et al 2015;Fukushima et al 2013). However, several P450s and glycosyltransferases involved in saponin biosynthesis still remain uncharacterized and in planta evidence for tentatively identified genes is minimal.…”
Section: Introductionmentioning
confidence: 99%